THU0439 52-Week Efficacy and Safety of Apremilast and Switch from Etanercept in Patients with Moderate To Severe Psoriasis: Results from The Liberate Study. (15th July 2016) - Reich, K.; Soung, J.; Gooderham, M.; Zhang, Z.; Nograles, K.; Day, R.M.; Ferris, L.; Goodfield, M.
Abstract : Background: Psoriasis is a chronic systemic inflammatory disease often treated with conventional systemic and biologic drugs that may variously be ineffective, inaccessible, or pose significant safety and tolerability risks. Objectives: The phase IIIb LIBERATE (Eval uati on in a Placeb o-Controlle d Study of Or al A premilast and E tanercept in Plaque Psoriasis) study (NCT01690299 ) evaluated the efficacy and safety of apremilast or etanercept vs. placebo in biologic-naive patients (pts) with moderate to severe plaque psoriasis. Methods: In this double-blind, double-dummy study, pts were randomized (1:1:1) to placebo (PBO), apremilast 30 mg BID (APR), or etanercept 50 mg QW (ETN) through Wk16; thereafter, all pts switched to or continued APR (PBO/APR, ETN/APR, APR/APR). The primary endpoint was achievement of a ≥75% reduction from baseline in Psoriasis Area and Severity Index (PASI) score (PASI-75) at Wk16 with APR vs. PBO; secondary endpoint was PASI-75 achievement at Wk16 with ETN vs. PBO. Additional physician global assessments (PGA) of disease activity were conducted using the static (sPGA), lattice system (LS-PGA), and scalp (ScPGA) instruments; nail disease was also evaluated (Nail Psoriasis Severity Index [NAPSI]). Responses were assessed at Wks16 and 52 using the last-observation-carried-forward (LOCF) methodology. Results: 250 pts received ≥1 dose of study drug, had both baseline PASI and ≥1 post-treatment PASI evaluations, and were included in the analysis set (PBO n=84; APR n=83; ETN n=83). At baseline, 166 (66.4%; PBO n=58; APR n=54; ETN n=54) pts had an ScPGA score ≥3 (moderate to very severe) and 148 (59.2%; PBO n=46; APR n=52; ETN n=50) had a NAPSI score ≥1. At Wk16, PASI-75 achievement was significantly greater ( P <0.0001) with APR (39.8%) or ETN (48.2%) vs. PBO (11.9%). Although this study was not designed/powered for APR vs. ETN comparisons, Wk16 PASI-75 achievement was not significantly different between APR and ETN ( P =0.2565, post hoc). At Wk16, APR and ETN produced significantly greater achievement of 0 or 1 ratings (clear or almost clear) vs. PBO in sPGA and LS-PGA and in ScPGA (clear or minimal) (Table ). Improvements in nail psoriasis were also achieved with APR and ETN at Wk16 (Table ). At Wk52, PASI-75 response was sustained in APR/APR (50.6%) and ETN/APR (55.4%) pts; PASI-75 response was 46.4% in PBO/APR pts (Table ). sPGA, LS-PGA, and ScPGA responses achieved at Wk16 were generally sustained through Wk52 with APR (Table ). Continued APR treatment over 52wks resulted in further improvements in nail psoriasis (Table ). Adverse events were consistent with known safety profiles of APR and ETN. Conclusions: APR demonstrated significant efficacy vs. PBO at Wk16; with continued APR treatment, therapeutic responses were generally sustained at Wk52. Efficacy was maintained in ETN pts who switched to APR. Disclosure of Interest: K. Reich Grant/research support from: Abbott, AbbVie, Amgen, Basilea, Biogen-Idec, Celgene, Centocor, Eli Lilly, Forward Pharma, GlaxoSmithKline, Janssen-Cilag, LEO Pharma, Medac, MSD (Essex Pharma, Schering-Plough), Novartis, Ocean Pharma, Pfizer (Wyeth), UCB, Consultant for: Abbott, AbbVie, Amgen, Basilea, Biogen-Idec, Celgene, Centocor, Eli Lilly, Forward Pharma, GlaxoSmithKline, Janssen-Cilag, LEO Pharma, Medac, MSD (Essex Pharma, Schering-Plough), Novartis, Ocean Pharma, Pfizer (Wyeth), UCB, Speakers bureau: Abbott, AbbVie, Amgen, Basilea, Biogen-Idec, Celgene, Centocor, Eli Lilly, Forward Pharma, GlaxoSmithKline, Janssen-Cilag, LEO Pharma, Medac, MSD (Essex Pharma, Schering-Plough), Novartis, Ocean Pharma, Pfizer (Wyeth), UCB, J. Soung Grant/research support from: Celgene, Amgen, Novartis, Galderma, Pfizer, Jannsen, Merz, Speakers bureau: Celgene, Amgen, AbbVie, M. Gooderham Grant/research support from: AbbVie, Allergan, Celgene, Eli Lilly, Galderma, Kythera, Leo Pharma, Merck, Novartis, Pfizer, Speakers bureau: AbbVie, Amgen, Astellas, Galderma, Janssen, Leo Pharma, Novartis, Pfizer, Z. Zhang Employee of: Celgene Corporation, K. Nograles Employee of: Celgene Corporation, R. Day Employee of: Celgene Corporation, L. Ferris Grant/research support from: Celgene Corporation, M. Goodfield Grant/research support from: Celgene Corporation